2016
DOI: 10.1038/nclimate3004
|View full text |Cite
|
Sign up to set email alerts
|

Greening of the Earth and its drivers

Abstract: Global environmental change is rapidly altering the dynamics of terrestrial vegetation, with consequences for the functioning of the Earth system and provision of ecosystem services 1,2 . Yet how global vegetation is responding to the changing environment is not well established. Here we use three long-term satellite leaf area index (LAI) records and ten global ecosystem models to investigate four key drivers of LAI trends during 1982-2009. We show a persistent and widespread increase of growing season integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

138
1,584
15
14

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 2,039 publications
(1,751 citation statements)
references
References 31 publications
138
1,584
15
14
Order By: Relevance
“…With increasing climate variability and more frequent occurrences of extreme events expected in the future 7 , research has targeted the sensitivity of ecosystems 8,9 . At the same time, recent studies have shown globally increasing leaf area index (LAI; a proxy for green vegetation cover) 10 , and aboveground biomass carbon (ABC) 11 , also known as the greening Earth 10,12 . Dynamic vegetation models and Earth observation studies reveal climatic and atmospheric changes as the main drivers of large scale increases in LAI 10,13 .…”
mentioning
confidence: 99%
“…With increasing climate variability and more frequent occurrences of extreme events expected in the future 7 , research has targeted the sensitivity of ecosystems 8,9 . At the same time, recent studies have shown globally increasing leaf area index (LAI; a proxy for green vegetation cover) 10 , and aboveground biomass carbon (ABC) 11 , also known as the greening Earth 10,12 . Dynamic vegetation models and Earth observation studies reveal climatic and atmospheric changes as the main drivers of large scale increases in LAI 10,13 .…”
mentioning
confidence: 99%
“…Here, we report relative reductions in G S driven by rising VPD on the order of 10% in most forest ecosystems, which would imply even greater relative reductions in canopy stomatal conductance since G S is influenced by soil conductance, which is not sensitive to VPD. While VPD and CO 2 concentrations are assumed to be independent drivers of stomatal conductance in theoretical formulations 17,19 , the extent to which their effects on stomatal conductance are additive remains an important topic for future work, which must also consider the confounding effects of increasing leaf area index 29 .…”
mentioning
confidence: 99%
“…szén-dioxid trágyázási effektus. Földi léptékben -űrfelvételek és ökoszisztéma modellek segítsé-gével -megállapították, hogy ez a hatás a levélfelület index (LAI) növekedésével mérhető "zöldülés" kiváltásában a múltban 70%-ban volt felelős, míg a N-trágyázási effektus csak 9%-ban (Zhu et al 2016). Ezt látszik igazolni az, hogy a fák a tanulmányban a melegedés és szárazodás hatására kimutatott növekedés-csökkenése ellenére az elmúlt időszakban gyorsabban nőttek, mint korábban (Somogyi 2008).…”
Section: öSszefoglaló éRtékelésunclassified